Sistema sredstv formirovanija special'noj podgotovlennosti junych sportsmenov na etapach mnogoletnej trenirovki v nastol'nom tennise - Matytsin, O. B. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The modern lines of development of the sports of top achievements require the regular perfection of scientific-theoretical and technological bases of long-term sports preparation. The next major factors stimulate the high rates of perfection in the systems of long-term preparation of athletes: - the globalization of the importance of the elite sports for the development of the world and national physical culture and the increase of its role in the life of civilized countries; - the increase of a level of professionalism of coaches, experts of scientific support of national teams training, and the managers of a physical culture and sports area; - the developing tendency of integration of Olympic and professional sports and the growth of popularity last as the perspective sphere of employment; - the fast increase of a competition in Olympic kinds of sports; - the intensive search of reserves of the growth of sports skill in elite athletes. The author shows the new technology to organize the long term sports training on the example of the young table tennis players aged 7-15.